Offering Subscriptions of Industrial Goods: Uncertain Experiment or Necessary Step? - Burger, Markus; Kruger, Andreas; Burgmann, Nils; Arlinghaus, Julia (IEEE transactions on engineering management, 2024)
The implementation of Industry 4.0 often entails various changes to a company's business model. Not all companies take advantage of the new technological capabilities or create new digital revenue streams. In this regard, subscription business models are growing more prevalent in the market for industrial goods. Although just a few pioneers have integrated subscription offerings in their portfolio so far, an increasing number of companies are considering doing the same. This article contributes to this subject by examining the transformation from a component supplier to a subscription service provider and its impact on customer relationships. The findings are drawn from three in-depth case studies, two interviews per each case and ten additional interviews with experts to gather further information. Agency theory provides the theoretical framework. We identify enablers and challenges of subscription business models during the consideration, implementation, and operation phase. This article provides practical insights into the transformation of a provider's business model in conjunction with subscription, thus benefiting companies in every step of the transformation process. Moreover, we contribute to the theoretical literature on Industry 4.0 and servitization by structuring the transformation toward a subscription business model in phases and correlate features with each phase.